PEDAGOGICAL COMMUNICATION AND COMMUNICATIVE FUNCTIONS - Khoshimova D. (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the professional activity of a teacher, in which educational tasks are solved through the interaction of a teacher with other participants in the educational process. the tasks and means of pedagogical influence and pedagogical communication of the teacher are shown.